Pembelajaran Berbasis Masalah (PBM) Dalam Pelajaran Sejarah di SMPN 3 Peureulak - Afwiyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The purpose of this study was to explore the Problem Based Learning (PBM) method in learning history at SMPN 3 Peureulak. This study uses a qualitative research method with a case study approach. Data collection was carried out through class observations, interviews with history teachers, and analysis of learning materials. The research participants consisted of two history teachers and 30 class VIII students of SMPN 3 Peureulak. The results showed that history teachers had designed student-centered learning activities by introducing complex historical issues and encouraging students to gather evidence and analyze historical information. The Problem-Based Learning Approach (PBM) in history learning at SMPN 3 Peureulak also has an impact on students, namely: increasing understanding of historical concepts, increasing student involvement, developing critical thinking skills, improving collaboration and communication skills, and introducing multiple perspectives.